Avaliação da expressão tecidual dos ligantes de morte programada-1 e -2, do receptor PD-1 e da resposta imunológica citotóxica no líquen plano oral - Gonçalves, Julie Ane Maria (2020)
Oral lichen planus (OLP) is a chronic autoimmune disease, mediated by T lymphocytes (TL) and characterized by apoptosis of basal/suprabasal keratinocytes. Although its etiopathogenesis is not completely elucidated, recent data reveal that blocking immunoregulatory molecules such as programmed death ligands (PD-Ls) and/or PD-1 receptor may promote the appearance of oral lichen planus-like lesions. It is classically established that this PD-Ls/PD-1 pathway contributes to evasion of neoplastic cells; however, it may be important in the regulation of helper and cytotoxic (CD8+) TL in autoimmune diseases. Objective: To investigate the tissue expression of PD-L1 and PD-L2 molecules, as well as PD-1+, CD8+ and granzyme B+ (GrB) cell populations in OLPs and whether there is a relationship between these immunoinhibitory proteins/cell populations and the severity of OLP. Material and methods: Samples of OLP patients (n = 23) were classified according to the histopathological criteria of the American Association of Oral and Maxillofacial Pathology (AAOMP/2016) and submitted to immunohistochemistry. Semi-quantitative (PD-L1+ and PD-L2+) and quantitative analysis (PD-1+, CD8+ and GrB+ cells) were performed. The severity of OLP was assessed by clinical subtype, symptomatology and response to corticosteroid therapy. Results: Most OLP samples were considered negative for PD-L1 (n = 14/22; 63.7%), however high PD-L2 expression (n = 19/22; 86.3%) by both keratinocytes and immunoinflammatory cells has been demonstrated. Low cytotoxic immune response (CD8/GrB ratio per mm2) was evidenced in OLP samples (subepithelial: 1047.4/140.6 and intraepithelial: 197.7/41.6). In addition, PD-1+/mm2 (subepithelial: 70.2 and intraepithelial: 7.4) cell density was reduced compared to CD8+/mm2 LT (subepithelial: 1047.4 and intraepithelial: 197.7) (p <0.01). There was a significantly lower number of GrB+ cells in the intraepithelial region in reticular OLP compared to erosive / bullous OLP (p = 0.03). Conclusions: The findings show that the PD-L1 / PD-1 pathway seems to be compromised in OLP due to low PD-L1 expression and PD-1 + cell scarcity in most samples. On the other hand, PD-L2 overexpression added to a possible regulation of cytotoxic immune response suggests an immune tolerance that may contribute to the chronic profile of OLP.